2021
DOI: 10.1021/acsami.1c06008
|View full text |Cite
|
Sign up to set email alerts
|

NH2-UiO-66 Coated with Two-Dimensional Covalent Organic Frameworks: High Stability and Photocatalytic Activity

Abstract: The poor stability and low catalytic activity of NH2-UiO-66 in basic solutions require the reactions to be conducted in acidic solutions, which seriously hinders its potential photocatalytic application. Herein, we report that NH2-UiO-66 coated with two-dimensional covalent organic frameworks (COFs) via imine bond connection presents not only high photocatalytic activity but also high stability and adaptability to the solution environment. The NH2-UiO-66/COF hybrid material was fabricated through the Schiff ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 59 publications
5
54
0
Order By: Relevance
“…18 The characteristic diffraction peaks at 2 θ = 11.1°, 12.7° and 20.4° in MC-24 correspond well to the MOF lattices (002), (111), and (113), demonstrating the formation of the MOF, while the diffraction peaks of the MOF were very weak, possibly due to the poorer crystallinity of MC-24. 48 The Raman spectra of MC-15-700, MC-24-700, and MC-33-700 all showed two typical characteristic peaks at around 1325 cm −1 (D band) and 1590 cm −1 (G band). The I D / I G ratios of MC-15-700, MC-24-700, and MC-33-700 were 0.96, 0.99, and 1.038, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…18 The characteristic diffraction peaks at 2 θ = 11.1°, 12.7° and 20.4° in MC-24 correspond well to the MOF lattices (002), (111), and (113), demonstrating the formation of the MOF, while the diffraction peaks of the MOF were very weak, possibly due to the poorer crystallinity of MC-24. 48 The Raman spectra of MC-15-700, MC-24-700, and MC-33-700 all showed two typical characteristic peaks at around 1325 cm −1 (D band) and 1590 cm −1 (G band). The I D / I G ratios of MC-15-700, MC-24-700, and MC-33-700 were 0.96, 0.99, and 1.038, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…When they are excited by incident light to produce electron–hole pairs, the photogenerated electrons are transferred from the CB of semiconductor 1 that has a high reduction potential to the CB of semiconductor 2 that has a low reduction potential. , These are the most common MOF-COF heterojunctions used to facilitate the separation of photogenerated electrons and holes. Both of the semiconductors are able to be excited by incident light, and the VB holes and CB electrons migrate to each other, effectively inhibiting the compounding of photogenerated electrons and photogenerated holes. , For example, our group introduced TAPT-TP-COF into a MOF to obtain a II-scheme heterojunction NH 2 -UiO-66@TAPT-TP-COF photocatalyst for photocatalytic H 2 evolution and eventually found that the maximum photocatalytic H 2 evolution rate was 8 times and 2 times higher than those of the pure MOF and COF, respectively …”
Section: Design Of Mof-cof Photocatalystsmentioning
confidence: 99%
“…(C) NH 2 -UiO-66/TAPT-TP-COF. Reproduced with permission . Copyright 2021 American Chemical Society.…”
Section: Mof-cof Synthesis Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work has shown that NH 2 -UiO-66 coupled with COF has high photocatalytic activity and good stability. 26 UiO-66 has good adsorption properties in aqueous environments. The adsorption capacity can be improved by doping with heterometallic modifications or post-synthetic modification strategies.…”
Section: Introductionmentioning
confidence: 99%